HAJ PERSPECTIVE ISLAMIC EDUCATION CONCEPTABDUL MALIK KARIM AMRULLAH (HAMKA) - Mukhlis; Eka Widya Putri (RADJA PUBLIKA, 2021)
This type of research is this research including the type of library research (library research),namely research whose object of study uses library data in the form of books as a data source. This study uses a phenomenological approach with data sources used in this writing are phenomena or events that occur in everyday life which focus on incidents of violence against women. The results of the research The relevance of the concept of educators according to Hamka with Islamic education today is still well oriented, especially on the role of educators and the obligations of every parent, teacher and community, which affect the habits and daily life of students. The purpose of Islamic education according to Hamka has relevance to contemporary education that the purpose of education is for students to receive the pleasure of Allah by having faith and fear of Him,